Effect of availability and COVID-19 vaccination on food shopping and consumption behaviors among Jordan universities students - Taybeh, Asma' O.; Osaili, Tareq M.; Al-Nabulsi, Anas A.; Ben Hassen, Tarek; Faour-Klingbeil, Dima; Cheikh Ismail, Leila; Olaimat, Amin N. (Frontiers in Sustainable Food Systems, 2022)
The COVID-19 pandemic influenced the lives of university students all across the globe. Indeed, the pandemic has impacted many aspects of their daily routine, changing their social and health habits and food-related behaviors. There is now no approved therapy, and vaccination is the only clinical preventative measure that provides the highest protection against the virus. While these vaccines have been beneficial in curbing the pandemic’s effect, they may also influence food-related behaviors. Accordingly, this paper aims to investigate the impact of vaccination availability on university students’ food shopping and consumption habits, vaccine-related opinions, and back on-campus behaviors in Jordan. The research is based on an online survey conducted in Jordan using a structured questionnaire and distributed through Google Forms between January 1 and March 20, 2022. A total of 624 valid answers were collected. The findings revealed no significant changes in the way students consumed, shopped, and handled food compared to the pre-vaccine period. However, there is a slight post-vaccine trend toward shopping more groceries online and ordering more meals via delivery apps and takeout services. Regarding health-related food choices, there was an increase in the consumption of healthy food, water, and fruits and vegetables. Further, following the availability of the vaccination, students’ adoption of COVID-19 food-related habits was maintained. Gender, engagement in food preparation activities, and living status (e.g., whether or not living with parents) substantially affected several food-related behaviors. The findings are expected to guide both current emergency preparations and long-term food-related policies in Jordan. This information may also be helpful to researchers interested in the effects of COVID-19 vaccination on student nutrition and related food behaviors.